Case report: Bronchoscopic intervention for rare benign airway tumors: a report of 4 cases and literature review - Cui, Zhifang; Wang, Jinhong; Wang, Hongwu; Li, Lei; Si, Xiaohui; Zhang, Yanbin; Zou, Heng (Frontiers in Oncology, 2024)
Due to their unique location, airway tumors have a significant impact on patient quality of life and survival. Current research has focused extensively on malignant airway tumors; however, benign airway tumors, especially rare ones, are less understood due to their low incidence. These tumors are often misdiagnosed and mistreated due to diagnostic challenges. Therefore, there is still a lack of consensus on the treatment of some rare benign airway tumors. Our center summarizes the diagnosis and treatment of four rare cases of benign airway stenosis in recent years, highlighting the bronchoscopic manifestations and therapeutic approaches to improve the understanding of these diseases.